Fluorescent anti-counterfeiting ink and preparation method thereof
By using rare earth-combined fluorescent materials and fatty acid-modified nanomaterial dispersants in fluorescent anti-counterfeiting inks, the problem of poor dispersion performance of fluorescent materials in ink connection materials is solved, and the high tolerance and uniform fluorescence effect of the ink is achieved.
Patent Information
- Application Number
- CN202411493089.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The fluorescent materials of existing fluorescent anti-counterfeiting inks have poor dispersion performance in the ink connection material, which affects the ink tolerance and leads to uneven decay of the fluorescent effect.
Using rare earth complex fluorescent materials, isocyanate and polycarbonate diol as the main raw materials, and rare earth complexes as luminescent components, a fluorescent material with both fluorescence effect and bonding ability is prepared, and dispersed by fatty acid modified nanomaterials. The agent improves dispersion performance.
It improves the tolerance of fluorescent anti-counterfeiting ink, makes the fluorescent effect decays uniformly in each area, has a good uniform anti-counterfeiting effect, and improves the fluorescent intensity and fluidity.
Smart Images

Figure BDA0005100588050000051 
Figure BDA0005100588050000061 
Figure BDA0005100588050000131
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fluorescent inks, and in particular to a fluorescent anti-counterfeiting ink and a preparation method thereof. Background Art
[0002] With the development of social economy, counterfeit products have become a serious social problem, which not only causes huge economic losses, but also poses great risks to the safety and health of consumers. Therefore, it is particularly important to develop advanced anti-counterfeiting methods to resist the circulation of counterfeit products. Fluorescent anti-counterfeiting method is a technology that uses fluorescent materials to display unique fluorescent effects under specific light to achieve anti-counterfeiting. Fluorescent materials will show specific colors under ordinary light, but can emit bright fluorescence under ultraviolet light. It is usually mixed with ink binders to produce fluorescent anti-counterfeiting inks, and then anti-counterfeiting patterns or texts are printed on products such as tickets that need to be anti-counterfeited, thereby ensuring the safety of the product and effectively resisting the circulation of counterfeit and shoddy products.
[0003] Fluorescent materials are mainly divided into inorganic, organic and rare earth complex types. Inorganic fluorescent materials are made of metal (zinc, chromium) sulfide trace active agents and calcined. They have good stability, but poor water resistance, and have a certain wear and corrosion effect on the surface of products that need to be treated for anti-counterfeiting. Although organic fluorescent materials have high water resistance, they have the problem of poor stability. Rare earth complex fluorescent materials have the best fluorescence intensity, which provides a prerequisite for the preparation of high-end fluorescent anti-counterfeiting inks. However, their poor dispersion in ink binders may affect the ink's tolerance (such as light resistance, heat resistance, and chemical solvent resistance, etc.), resulting in a faster decay of the fluorescence effect in certain areas of the printed part. Therefore, the tolerance of fluorescent anti-counterfeiting inks is crucial to the anti-counterfeiting effect. Summary of the invention
[0004] In order to solve the above technical problems, the present application provides a fluorescent anti-counterfeiting ink and a preparation method thereof.
[0005] In the first aspect, the present application provides a fluorescent anti-counterfeiting ink, which adopts the following technical solution: the raw materials used include a rare earth complex fluorescent material, an ink vehicle, ethyl acetate, a defoamer and an antioxidant in a weight ratio of (30-60): (20-50): 16: 2: 2, the raw materials used for the rare earth complex fluorescent material include a rare earth complex, isocyanate and polycarbonate diol in a molar ratio of 1: (2.8-3): 1, and the preparation method thereof is as follows: The rare earth complex is dispersed in an organic solvent, and then isocyanate is added, heated and stirred, and the organic solvent is added after the temperature reaction, and then polycarbonate diol is added to the system, and the reaction is continued. Finally, a chain extender and a capping agent are added to obtain a rare earth complex fluorescent material.
[0006] By adopting the above-mentioned technical scheme, the present application utilizes isocyanate and polycarbonate diol as the main raw materials and rare earth complex as the luminescent component to prepare a rare earth complex fluorescent material having both fluorescent effect and bonding ability. The rare earth complex fluorescent material has good dispersion ability in the fluorescent anti-counterfeiting ink and can form a uniform dispersion system after being mixed with the ink binder of the present application, so that the finally obtained fluorescent anti-counterfeiting ink has good tolerance. Therefore, it can ensure that the fluorescence effect decay rate of each area of the printed part is uniform during application, and has a good uniform anti-counterfeiting effect.
[0007] In addition, the present application bonds the components of the rare earth complex fluorescent material. When preparing the rare earth complex fluorescent material, the small molecules of the isocyanate and the polycarbonate diol can form a uniform arrangement, and the small molecules of the rare earth complex are separated one by one, so that the fluorescent segments of the rare earth complex fluorescent material finally obtained have a certain distance between each other. Compared with directly blending the rare earth complex fluorescent material with other components, the bonding method effectively reduces the possibility of easy aggregation of the fluorescent segments and thus fluorescence quenching, thereby reducing the possibility of damage to the fluorescence intensity, so that the fluorescent anti-counterfeiting ink of the present application has good fluorescence intensity. The isocyanate in the specific implementation manner of the present application is illustrated by taking isophorone diisocyanate as an example, and those skilled in the art can make adjustments according to actual conditions.
[0008] In summary, the various components of the raw materials used in the rare earth complex fluorescent material of the present application fully exert their synergistic effect, so that the final fluorescent anti-counterfeiting ink has both high tolerance and fluorescence intensity. Tests have shown that its heat resistance level, light resistance level and ethanol resistance level are all greater than or equal to 3, which effectively expands the scope of application of the fluorescent anti-counterfeiting ink and improves its competitiveness.
[0009] Preferably, the raw materials used for the rare earth complex include rare earth oxide, dimethylolpropionic acid, α-thenoyltrifluoroacetone and o-phenanthroline in a molar ratio of (2-2.2):4:8:4.
[0010] The method for preparing the rare earth complex comprises the following steps: The rare earth oxide is dispersed in a hydrochloric acid solution, heated and stirred until the solution becomes transparent, and then the temperature is continued to be raised to a nearly dry state to remove excess hydrochloric acid to obtain rare earth crystals, which are then mixed with dihydroxymethylpropionic acid, and the pH is adjusted to 6-7 after a period of reaction, and the reaction is continued, and then α-thiophenoyltrifluoroacetone is added, and the pH is adjusted to 6-7 again, and o-phenanthroline is added after a period of reaction, and the solvent is evaporated after a period of reaction, and centrifuged to obtain a solid substance, which is washed and vacuum dried to obtain a rare earth complex.
[0011] Preferably, the rare earth oxides include europium oxide, gadolinium oxide and ytterbium oxide.
[0012] Optionally, the molar ratio of europium oxide, gadolinium oxide and ytterbium oxide is 1:(6-6.5):(2.5-3).
[0013] Preferably, the molar ratio of europium oxide, gadolinium oxide and ytterbium oxide is 1:6.2:2.8.
[0014] By adopting the above technical scheme, the present application uses dimethylolpropionic acid, α-thiopheneyl trifluoroacetone and o-phenanthroline as ligands, blends with rare earth oxides with fluorescent effects and prepares rare earth complexes, which have both high fluorescence intensity and the property of being bonded to isocyanate, and the present application further optimizes the components and the proportion of each component of the rare earth oxides, and the rare earth complex prepared by europium oxide, gadolinium oxide and ytterbium oxide has a good co-fluorescence effect inside, and the above three rare earth oxides are blended, and the fluorescence intensity of the rare earth complex finally obtained is much greater than that of the rare earth complex prepared by other combinations. Finally, the present application strictly controls the molar ratio of europium oxide, gadolinium oxide and ytterbium oxide, further improving its fluorescence intensity.
[0015] Preferably, the weight ratio of the rare earth complex fluorescent material, the ink vehicle, ethyl acetate, the defoaming agent and the antioxidant is 50:30:16:2:2.
[0016] By adopting the above-mentioned technical scheme, the present application strictly controls the weight ratio of rare earth complex fluorescent materials, ink binders, ethyl acetate, defoaming agents and antioxidants, so that the internal dispersion uniformity, fluorescence intensity and rheological properties of the finally prepared fluorescent anti-counterfeiting ink are more balanced and at a high level. Experimental data show that at this time, the fluorescence intensity of the fluorescent anti-counterfeiting ink is 380.9au, the fineness is 8.0um, and the fluidity is 28.0mm.
[0017] Preferably, the raw materials used also include a fatty acid modified nano material dispersant, and the weight ratio of the fatty acid modified nano material dispersant to the total weight of other raw materials used is (11-12):100.
[0018] Preferably, the fatty acid modified nano material dispersant is prepared by the following method, specifically: The nanomaterial is heated, and then fatty acid is added to react, filtered, dried, and ball-milled to obtain a fatty acid-modified nanomaterial dispersant, wherein the weight ratio of the nanomaterial to the fatty acid is 100:(3-4).
[0019] Optionally, the fatty acid comprises sodium stearate and / or palmitic acid.
[0020] In the specific embodiment of the present application, the nanomaterial takes nano calcium carbonate slurry as an example, and the specific preparation method is as follows: calcium hydroxide is placed in a supergravity micro-interface reactor, and a circulation pump and a cooling device are turned on at a temperature of 25°C and a volume flow rate of 3m 2 / h, carbon dioxide was continuously introduced until the pH in the system was 7, thereby obtaining a nano-calcium carbonate slurry.
[0021] By adopting the above technical scheme, the present application adds a fatty acid-modified nanomaterial dispersant into the system, which has the effect of promoting the dispersion of rare earth complex fluorescent materials in the ink vehicle, and can further improve the internal uniformity of the fluorescent anti-counterfeiting ink. The modification treatment of the present application coats an acid layer on the particle surface of the nanomaterial, effectively increasing the number of its surface active groups, thereby improving the hydrophobicity and lipophilicity of the nanomaterial and the dispersion ability in the ink system. Therefore, the fatty acid-modified nanomaterial dispersant of the present application can act as a bridge in the system, not only has a good dispersion effect itself, but also can promote further blending of other components in the system. After adding it to the fluorescent anti-counterfeiting ink, the fineness of the overall system can be reduced to no more than 5.5um, and the fluidity can be improved to no less than 33.0mm.
[0022] In addition, the present application strictly controls the weight ratio of nanomaterials to fatty acids. If the amount of fatty acid added is too large, the acid layer coating on the surface of the nanomaterial is already saturated, and further addition will reduce the dispersion ability of the nanomaterial; if the amount of fatty acid added is too small, the acid layer coating on the surface of the nanomaterial is insufficient and cannot achieve an effective modification effect.
[0023] Preferably, the fatty acid comprises sodium stearate and palmitic acid.
[0024] By adopting the above technical scheme, the present application further controls the composition of fatty acids. Sodium stearate and palmitic acid are mixed to form a eutectic mixture. The two work together to give full play to the synergistic effect. Compared with the modification effect when used alone, the fineness and fluidity are further improved.
[0025] Optionally, the weight ratio of sodium stearate to palmitic acid is (1-3):(1-4).
[0026] Preferably, the weight ratio of sodium stearate to palmitic acid is 1:1.
[0027] By adopting the above technical solution, the present application strictly controls the weight ratio of sodium stearate and palmitic acid. Experimental data show that when the weight ratio of sodium stearate and palmitic acid is 1:1, the fineness of the fluorescent anti-counterfeiting ink can be as low as 4.0um and the fluidity can reach 38.5mm.
[0028] In a second aspect, the present application provides a method for preparing a fluorescent anti-counterfeiting ink, comprising the following steps: uniformly mixing all the raw materials used, and finally obtaining the fluorescent anti-counterfeiting ink.
[0029] In summary, this application has the following beneficial technical effects: 1. The raw materials of the rare earth complex fluorescent material of the present application give full play to the synergistic effect between the components, so that the final fluorescent anti-counterfeiting ink has both high tolerance and fluorescence intensity. Tests have shown that its heat resistance level is not less than 3, light resistance level is not less than 3, and ethanol resistance level is not less than 3, which effectively expands the scope of application of fluorescent anti-counterfeiting ink and improves its competitiveness; 2. The present application adds a fatty acid-modified nanomaterial dispersant into the system, which has the effect of promoting the dispersion of rare earth complex fluorescent materials in ink binders, and can further improve the internal uniformity of fluorescent anti-counterfeiting inks. The present application also uses fatty acids to modify nanomaterials, coats the surface of nanomaterial particles with an acid layer, and increases the number of surface active groups, thereby improving the hydrophobicity and lipophilicity of the nanomaterials and the dispersibility in the ink system. Therefore, the fatty acid-modified nanomaterial dispersant of the present application can play a bridging role in the system, not only having a good dispersing effect itself, but also promoting further blending of other components in the system; 3. The preparation method of the present application has simple steps and can be produced in large quantities, thus having high practical value. DETAILED DESCRIPTION
[0030] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Dimethylolpropionic acid was purchased from Aladdin Reagent Co., Ltd., CAS 4767-03-7; α-Thenoyltrifluoroacetone was purchased from Aladdin Reagent Co., Ltd., CAS 326-91-0; O-phenanthroline was purchased from Aladdin Reagent Co., Ltd., CAS 5411-89-8; Europium oxide was purchased from Aladdin Reagent Co., Ltd., CAS1308-96-9; Gadolinium oxide was purchased from Aladdin Reagent Co., Ltd., CAS12064-62-9; Ytterbium oxide was purchased from Aladdin Reagent Co., Ltd., CAS1314-37-0; Lutetium oxide was purchased from Aladdin Reagent Co., Ltd., CAS12032-20-1; Isophorone diisocyanate was purchased from Aladdin Reagent Co., Ltd., CAS 4098-71-9; Polycarbonate diol was purchased from Jining Huakai Resin Co., Ltd., with a molecular weight of 1500; Ethyl acetate was purchased from Hunan Huihong Reagent Co., Ltd.; Dibutyltin dilaurate was purchased from Hunan Huihong Reagent Co., Ltd., CAS 77-58-7; 1,4-Butanediol chain extender was purchased from Aladdin Reagent Co., Ltd., CAS110-63-4; Isopropanol capping agent was purchased from Aladdin Reagent Co., Ltd.; Sodium stearate was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., CAS 822-16-2; Palmitic acid was purchased from Shanghai Yuanye Biotechnology Co., Ltd., CAS 57-10-3; The ink binder was purchased from Suzhou Aolaixin Building Materials Co., Ltd., with the brand name JL-SX; The antioxidant was DBD antioxidant purchased from Guangzhou Dachuan Fine Chemical Co., Ltd.; The defoaming agent was PDMS defoaming agent purchased from Guangzhou Dachuan Fine Chemical Co., Ltd.
[0031] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0032] Preparation Examples 1.1-1.10 The method for preparing a rare earth complex comprises the following steps: Disperse rare earth oxides in a 1:1 hydrochloric acid solution, heat and stir until the solution becomes transparent, then continue to heat to 85°C until the system is nearly dry to remove excess hydrochloric acid to obtain rare earth crystals, transfer them into a container with a constant pressure filter, magnetic stirring and heating device with anhydrous ethanol, mix them with dihydroxymethylpropionic acid at a temperature of 45°C, react for 0.5h, adjust the pH to between 6 and 7, continue to react for 1.25h, then add 8mol / L α-thiophenoyltrifluoroacetone ethanol solution, adjust the pH again to between 6 and 7, add 4mol / L o-phenanthroline ethanol solution after reacting for 1h, evaporate and remove the solvent after reacting for 1h, centrifuge to obtain a solid substance, wash it with water three times, wash it with alcohol three times, then centrifuge it, and vacuum dry it at a temperature of 65°C to obtain a rare earth complex. The specific components of the rare earth oxides and the amounts of each substance are shown in Table 1.1.
[0033] Table 1.1 Specific components and amounts of each substance in the rare earth oxides of Preparation Examples 1.1-1.10 Preparation Example 1.11 The preparation method of the rare earth complex is different from that of Preparation Example 1.1 in that 1 mol of europium oxide is 0.5 mol, 1 mol of gadolinium oxide is 0.25 mol, and 1 mol of ytterbium oxide is 0.25 mol. The rest is the same as Preparation Example 1.1.
[0034] Preparation Example 1.12 The preparation method of the rare earth complex is different from that of Preparation Example 1.1 in that 1 mol of europium oxide is 2 mol, 1 mol of gadolinium oxide is 1 mol, and 1 mol of ytterbium oxide is used, and the rest is the same as Preparation Example 1.1.
[0035] Preparation Example 2.1 The method for preparing a rare earth complex fluorescent material comprises the following steps: 1 mol of the rare earth complex prepared in Preparation Example 1.1 was dispersed in 6 L of ethyl acetate to obtain a suspension, and 5 g of dibutyltin dilaurate was added, followed by 3 mol of isophorone diisocyanate. The mixture was stirred at 45 °C for 0.5 h, and then the temperature was raised to 65 °C for reaction for 3 h. 6 L of ethyl acetate was added, 1 mol of polycarbonate diol was added, and then 6 L of ethyl acetate and 5 g of dibutyltin dilaurate were added. After the reaction was continued for 4 h, 1 mol of 1,4-butanediol chain extender was added to the system, and the reaction was continued for 2 h. Finally, 5 L of isopropanol end-capping agent was added to obtain a rare earth complex fluorescent material.
[0036] Preparation Example 2.2 The method for preparing a rare earth complex fluorescent material comprises the following steps: Disperse 1 mol of the rare earth complex prepared in Preparation Example 1.2 in 6 L of ethyl acetate to obtain a suspension, add 5 g of dibutyltin dilaurate, and then add 2.9 mol of isophorone diisocyanate, stir at 45 ° C for 0.5 h, then heat to 65 ° C for reaction for 3 h, add 6 L of ethyl acetate, add 1 mol of polycarbonate diol, then add 6 L of ethyl acetate and 5 g of dibutyltin dilaurate, continue to react for 4 h, add 1 mol of 1,4-butanediol chain extender into the system, react for 2 h, and finally add 5 L of isopropanol end-capping agent to obtain a rare earth complex fluorescent material.
[0037] Preparation Example 2.3 The method for preparing a rare earth complex fluorescent material comprises the following steps: 1 mol of the rare earth complex prepared in Preparation Example 1.1 was dispersed in 6 L of ethyl acetate to obtain a suspension, and 5 g of dibutyltin dilaurate was added, followed by 2.8 mol of isophorone diisocyanate. The mixture was stirred at 45 °C for 0.5 h, and then the temperature was raised to 65 °C for reaction for 3 h. 6 L of ethyl acetate was added, 1 mol of polycarbonate diol was added, and then 6 L of ethyl acetate and 5 g of dibutyltin dilaurate were added. After the reaction was continued for 4 h, 1 mol of 1,4-butanediol chain extender was added to the system, and the reaction was continued for 2 h. Finally, 5 L of isopropanol end-capping agent was added to obtain a rare earth complex fluorescent material.
[0038] Preparation Examples 2.4-2.13 The method for preparing rare earth complex fluorescent materials is different from that of Preparation Example 2.1 in that the rare earth complex prepared in Preparation Example 1.1 is replaced by the rare earth complexes prepared in Preparation Examples 1.3-1.12 respectively, and the rest is the same as Preparation Example 1.1.
[0039] Preparation Example 3.1 The preparation method of the fatty acid modified nano material dispersant comprises the following steps: 500g of calcium hydroxide was placed in a high gravity microinterface reactor, and the circulation pump and cooling device were turned on at a temperature of 25°C and a volume flow rate of 3m 2 / h, carbon dioxide was continuously introduced until the pH value in the system was 7 to obtain nano calcium carbonate slurry; all the nano calcium carbonate slurry was heated to 70°C, and then 20g fatty acid was added to react for 40min, the solid was filtered to obtain a solid, dried, and ball-milled to a particle size of less than 70nm to obtain a fatty acid-modified nano material dispersant, wherein the specific components and amounts of the fatty acids are shown in Table 1.2.
[0040] Preparation Example 3.2 The preparation method of the fatty acid modified nano material dispersant comprises the following steps: 500g of calcium hydroxide was placed in a high gravity microinterface reactor, and the circulation pump and cooling device were turned on at a temperature of 25°C and a volume flow rate of 3m 2 / h, carbon dioxide was continuously introduced until the pH value in the system was 7 to obtain nano calcium carbonate slurry; all the nano calcium carbonate slurry was heated to 70°C, and then 15g of fatty acid was added to react for 40min, the solid was filtered to obtain a solid, dried, and ball-milled to a particle size of less than 70nm to obtain a fatty acid-modified nano material dispersant, wherein the specific components and amounts of the fatty acids are shown in Table 1.2.
[0041] Preparation Example 3.3 The preparation method of the fatty acid modified nano material dispersant comprises the following steps: 500g of calcium hydroxide was placed in a high gravity microinterface reactor, and the circulation pump and cooling device were turned on at a temperature of 25°C and a volume flow rate of 3m 2 / h, carbon dioxide was continuously introduced until the pH value in the system was 7 to obtain nano calcium carbonate slurry; all the nano calcium carbonate slurry was heated to 70°C, and then 17.5g fatty acid was added to react for 40min, and the solid was filtered to obtain a solid, dried, and ball-milled to a particle size of less than 70nm to obtain a fatty acid-modified nano material dispersant, wherein the specific components and amounts of the fatty acids are shown in Table 1.2.
[0042] Preparation Example 3.4 The preparation method of the fatty acid modified nano material dispersant comprises the following steps: 500g of calcium hydroxide was placed in a high gravity microinterface reactor, and the circulation pump and cooling device were turned on at a temperature of 25°C and a volume flow rate of 3m 2 / h, carbon dioxide was continuously introduced until the pH value in the system was 7 to obtain nano calcium carbonate slurry; all the nano calcium carbonate slurry was heated to 70°C, and then 12g of fatty acid was added to react for 40min, the solid was filtered to obtain a solid, dried, and ball-milled to a particle size of less than 70nm to obtain a fatty acid-modified nano material dispersant, wherein the specific components and amounts of the fatty acid are shown in Table 1.2.
[0043] Preparation Example 3.5 The preparation method of the fatty acid modified nano material dispersant comprises the following steps: 500g of calcium hydroxide was placed in a high gravity microinterface reactor, and the circulation pump and cooling device were turned on at a temperature of 25°C and a volume flow rate of 3m 2 / h, carbon dioxide was continuously introduced until the pH value in the system was 7 to obtain nano calcium carbonate slurry; all the nano calcium carbonate slurry was heated to 70°C, and then 25g fatty acid was added to react for 40min, the solid was filtered to obtain a solid, dried, and ball-milled to a particle size of less than 70nm to obtain a fatty acid-modified nano material dispersant, wherein the specific components and amounts of the fatty acids are shown in Table 1.2.
[0044] Preparation Examples 3.6-3.12 The preparation method of fatty acid modified nanomaterial dispersant is different from that of Preparation Example 3.1 in that the specific components and dosage of the fatty acid are different, as shown in Table 1.2 for details.
[0045] Table 1.2 Specific components and amounts of fatty acids in Preparation Examples 3.1-3.12 Preparation Example Specific components and dosage of fatty acids (kg) 3.1 12g sodium stearate and 8g palmitic acid 3.2 10g sodium stearate and 5g palmitic acid 3.3 10g sodium stearate and 7.5g palmitic acid 3.4 8g sodium stearate and 4g palmitic acid 3.5 15g sodium stearate and 10g palmitic acid 3.6 20g sodium stearate 3.7 20g palmitic acid 3.8 5g sodium stearate and 15g palmitic acid 3.9 15g sodium stearate and 5g palmitic acid 3.10 10g sodium stearate and 10g palmitic acid 3.11 7.5g sodium stearate and 12.5g palmitic acid 3.12 12.5g sodium stearate and 7.5g palmitic acid Comparative Preparation Example 1.1 The difference from Preparation Example 2.1 is: The amount of isophorone diisocyanate used was 2.5 mol, and the rest was the same as in Preparation Example 2.1.
[0046] Comparative Preparation Example 1.2 The difference from Preparation Example 2.1 is: The amount of isophorone diisocyanate used was 3.5 mol, and the rest was the same as in Preparation Example 2.1.
[0047] Comparative Preparation Example 1.3 The difference from Preparation Example 2.1 is that the polycarbonate diol is removed, specifically: 1 mol of the rare earth complex prepared in Preparation Example 1.1 was dispersed in 6 L of ethyl acetate to obtain a suspension, and then 5 g of dibutyltin dilaurate was added, followed by 3 mol of isophorone diisocyanate. The mixture was stirred at 45 °C for 0.5 h, and then the temperature was raised to 65 °C for reaction for 3 h. After continuing the reaction for 2 h, 1 mol of 1,4-butanediol chain extender was added to the system, and the reaction was continued for 2 h. Finally, 3 L of isopropanol capping agent was added to obtain a rare earth complex fluorescent material.
[0048] Comparative Preparation Example 1.4 The difference from Preparation Example 2.1 is that isophorone diisocyanate is removed, specifically: 1 mol of the rare earth complex prepared in Preparation Example 1.1 was dispersed in 6 L of ethyl acetate to obtain a suspension, and then 5 g of dibutyltin dilaurate was added, followed by 2 mol of polycarbonate diol. The mixture was stirred at 45 °C for 0.5 h, and then the temperature was raised to 65 °C for reaction for 3 h. After continuing the reaction for 2 h, 0.7 mol of 1,4-butanediol chain extender was added to the system, and the reaction was continued for 2 h. Finally, 2 L of isopropanol end-capping agent was added to obtain a rare earth complex fluorescent material.
[0049] Examples 1.1-1.6 A method for preparing a fluorescent anti-counterfeiting ink comprises the following steps: weighing the rare earth complex fluorescent material and ink vehicle prepared in Preparation Examples 2.1-2.3 according to the amounts in Table 2.1, then first adding all the ink vehicle into a container, and then sequentially adding all the rare earth complex fluorescent material, 160g of ethyl acetate, 20g of an antioxidant and 20g of a defoaming agent, mixing evenly, and stirring under ultrasonic conditions for 40 minutes to obtain the fluorescent anti-counterfeiting ink.
[0050] Table 2.1 Raw material dosage of Examples 1.1-1.6 (g) Example Rare earth complex fluorescent material Ink vehicle 1.1 300 (Preparation Example 2.1) 500 1.2 450 (Preparation Example 2.2) 350 1.3 600 (Preparation Example 2.3) 200 1.4 500 (Preparation Example 2.1) 300 1.5 400 (Preparation Example 2.1) 400 1.6 550 (Preparation Example 2.1) 250 Examples 2.1-2.10 A method for preparing fluorescent anti-counterfeiting ink, which is different from Example 1.1 in that the rare earth complex fluorescent material prepared in Preparation Example 2.1 is replaced by the rare earth complex fluorescent materials prepared in Preparation Examples 2.4-2.13 respectively, and the rest is the same as Example 1.1.
[0051] Example 3.1 A method for preparing fluorescent anti-counterfeiting ink is different from Example 1.1 in that 110 g of fatty acid modified nanomaterial dispersant prepared in Preparation Example 3.1 is also added to blend with other raw materials, and the order of addition is before the rare earth complex fluorescent material. The rest is the same as Example 1.1.
[0052] Example 3.2 A method for preparing a fluorescent anti-counterfeiting ink is different from Example 1.1 in that 115 g of the fatty acid-modified nanomaterial dispersant prepared in Preparation Example 3.2 is added and blended with other raw materials, and the order of addition is before the rare earth complex fluorescent material. The rest is the same as Example 1.1.
[0053] Example 3.3 A method for preparing fluorescent anti-counterfeiting ink is different from Example 1.1 in that 120 g of fatty acid-modified nanomaterial dispersant prepared in Preparation Example 3.3 is added and blended with other raw materials, and the order of addition is before the rare earth complex fluorescent material. The rest is the same as Example 1.1.
[0054] Example 3.4 A method for preparing fluorescent anti-counterfeiting ink is different from Example 1.1 in that 100 g of fatty acid modified nanomaterial dispersant prepared in Preparation Example 3.1 is also added to blend with other raw materials, and the order of addition is before the rare earth complex fluorescent material. The rest is the same as Example 1.1.
[0055] Example 3.5 A method for preparing fluorescent anti-counterfeiting ink is different from Example 1.1 in that 130g of fatty acid modified nanomaterial dispersant prepared in Preparation Example 3.1 is also added to blend with other raw materials, and the order of addition is before the rare earth complex fluorescent material. The rest is the same as Example 1.1.
[0056] Examples 3.6-3.14 A method for preparing a fluorescent anti-counterfeiting ink, which is different from Example 3.1 in that the fatty acid-modified nanomaterial dispersant prepared in Preparation Example 3.1 is replaced by the fatty acid-modified nanomaterial dispersants prepared in Preparation Examples 3.4-3.12, respectively, and the rest is the same as Example 3.1.
[0057] Comparative Example 1 S1. Disperse 2 mol of europium oxide in 50 L of a 1:1 hydrochloric acid solution, heat and stir until the solution becomes transparent, then continue to heat to 85°C until the system is nearly dry to remove excess hydrochloric acid to obtain europium oxide crystals, transfer them into a container with a constant pressure filter, a magnetic stirring device and a heating device with anhydrous ethanol, mix them with 1 L of a 1.34 mol / L α-thiophenoyltrifluoroacetone ethanol solution at a temperature of 45°C, adjust the pH to between 6 and 7, react for 1 h, add 1 L of a 4 mol / L o-phenanthroline ethanol solution, react for 1 h, evaporate to remove the solvent, centrifuge to obtain a solid, wash it three times with water, wash it three times with alcohol, centrifuge it, and dry it in vacuo at a temperature of 65°C to obtain a rare earth complex; S2, dispersing 1 mol of the rare earth complex prepared in step S1 in 6 L of ethyl acetate to obtain a suspension, adding 1 mol of polycarbonate diol, and then adding 5 g of dibutyltin dilaurate, stirring evenly, slowly adding 2 mol of isophorone diisocyanate, reacting at a temperature of 65° C. for 0.5 h, adding 10 g of dibutyltin dilaurate, continuing the reaction for 3 h, and then adding 1 mol of 1,4-butanediol chain extender into the system, reacting for 1 h, and finally obtaining a rare earth-doped fluorescent material; S3. Add 300 g of the rare earth-doped fluorescent material prepared in step S2 into 500 g of the ink vehicle, and then add 160 g of ethyl acetate, 20 g of an antioxidant and 20 g of a defoaming agent in sequence, mix well, and stir under ultrasonic conditions for 40 minutes to obtain a fluorescent anti-counterfeiting ink.
[0058] Comparative Examples 2.1-2.4 The difference from Example 1.1 is that the rare earth complex fluorescent material prepared in Preparation Example 2.1 is replaced by the rare earth complex fluorescent materials prepared in Comparative Preparation Examples 1.1-1.4 respectively, and the rest is the same as Example 1.1.
[0059] Comparative Example 2.5 The difference from Example 1.1 is that the amount of rare earth complex fluorescent material prepared in Preparation Example 2.1 is 650g, the amount of ink vehicle is 150g, and the rest is the same as Example 1.1.
[0060] Comparative Example 2.6 The difference from Example 1.1 is that the amount of rare earth complex fluorescent material prepared in Preparation Example 2.1 is 250g, the amount of ink vehicle is 550g, and the rest is the same as Example 1.1.
[0061] Performance Testing 1. Dispersion effect: a. Fineness: According to the national standard GB / T 13217.3, take a small amount of fluorescent anti-counterfeiting ink and use a scraper fineness meter to scrape it from top to bottom. The fineness is expressed in um and recorded in Table 3; b. Fluidity: According to the national standard GB / T 14624.3, take 1 mL of fluorescent anti-counterfeiting ink, put it in the fluidity tester, cover it with a glass sheet, put a weight on it, read the value after 15 minutes, measure the sample with a ruler, and expand the diameter. The diameter represents the fluidity (mm), and record it in Table 3; 2. Tolerance: Take the fluorescent anti-counterfeiting ink of the embodiment and the comparative example, use the printability meter to make a print with an ink layer thickness of 1.5 um on a non-fluorescent print paper, make 5 prints for each group, and cut each print into two 20 mm × 30 mm rectangles after air-drying for 24 hours for standby use; a. Heat resistance: Place one rectangular printed sample in a 100°C oven and heat for 30 minutes. Do not dry the other printed sample. Take out the dried printed sample and cool it to room temperature. Then compare it with the other printed sample. Record the rating results in Table 3. b. Lightfastness: Cover one of the rectangular printed samples and the blue wool standard sample with black board paper and white writing paper, and expose them to the sun in a solarium. Then take them out and put them in a dark place for 30 minutes. Then compare them with the other printed sample and record the rating results in Table 3. c. Ethanol resistance: Soak one of the rectangular prints in ethanol for 30 minutes and place it on filter paper. Compare it with the other print and record the rating results in Table 3. Rating standard: It is divided into 5 levels according to the characteristics of the printed sample. The best level is level 5, which shows no change in fluorescence, level 4 shows a slight decrease in fluorescence, level 3 shows a significant decrease in fluorescence, level 2 shows only traces of fluorescence, and level 1 shows no fluorescence. 3. Anti-counterfeiting effect: a. Fluorescence intensity: The fluorescence intensity (au) of the ink in the fluorescence range was measured by fluorescence spectrum test method, and the results were recorded in Table 3.
[0062] Table 3 Test results Data Analysis: As can be seen from Table 3, the fineness of the fluorescent anti-counterfeiting ink of Examples 1.1-1.6 is 7.5-9.0um, the fluidity is 27.0-29.0mm, the heat resistance level is 3-4, the light resistance level is 3-4, the ethanol resistance level is 3, and the fluorescence intensity is 315.6-396.4au, which proves that the raw materials used in the rare earth complex fluorescent material of the present application fully play the role of coordination, so that the final fluorescent anti-counterfeiting ink has both high tolerance and fluorescence intensity, which effectively expands the scope of application of the fluorescent anti-counterfeiting ink and improves its competitiveness; The fluorescence intensity of Examples 2.1-2.4 is significantly lower than that of Example 1.1, which proves that the present application optimizes the components and the distribution ratio of the rare earth oxides, and the rare earth complex prepared by europium oxide, gadolinium oxide and ytterbium oxide has a good co-fluorescence effect. The above three rare earth oxides are mixed, and the fluorescence intensity of the rare earth complex finally obtained can be much greater than the fluorescence intensity of the rare earth complex prepared by other combinations. The fluorescence intensity of Examples 2.5-2.8 is significantly higher than that of Example 1.1, and the fluorescence intensity of Example 2.8 reaches 345.6 au, proving that the present application further improves its fluorescence intensity by controlling the weight ratio of europium oxide, gadolinium oxide and ytterbium oxide; The fluorescence intensity of Examples 2.9-2.10 is significantly lower than that of Example 1.1, which proves that the present application further improves its fluorescence intensity by controlling the weight ratio of rare earth oxide, dimethylolpropionic acid, α-thenoyltrifluoroacetone and o-phenanthroline; The fineness of Examples 3.1-3.3 is significantly lower than that of Example 1.1, and the fluidity, heat resistance level, light resistance level and ethanol resistance level are significantly higher than those of Example 1.1, which proves that the present application can play a bridging role in the system by adding a fatty acid-modified nanomaterial dispersant that has the effect of promoting the dispersion of rare earth complex fluorescent materials in the ink vehicle, and not only has a good dispersion effect itself, but also can promote further blending of other components in the system, so that the final fluorescent anti-counterfeiting ink has high dispersion uniformity and high tolerance; The fineness of Examples 3.4-3.5 is higher than that of Example 3.1, and the fluidity, heat resistance level, light resistance level, and ethanol resistance level are lower than those of Example 3.1, which proves that the present application further improves its ability to promote uniform dispersion by strictly controlling the amount of fatty acid-modified nanomaterial dispersant added; The fineness of Examples 3.6-3.7 is higher than that of Example 3.1, and the fluidity, heat resistance level, light resistance level and ethanol resistance level are lower than those of Example 3.1, which proves that the present application further optimizes the modification effect of fatty acids on nanomaterials by strictly controlling the weight ratio of nanomaterials to fatty acids, and further enhances its ability to promote uniform dispersion; The fineness of Examples 3.8-3.9 is higher than that of Example 3.1, and the fluidity, heat resistance level, light resistance level and ethanol resistance level are lower than those of Example 3.1, which proves that the present application further optimizes the modification effect of fatty acids on nanomaterials by strictly controlling the composition of fatty acids, and further improves its ability to promote uniform dispersion; Among Examples 3.10-3.14, Example 12 has the lowest fineness, and the highest fluidity, heat resistance, light resistance, and ethanol resistance, proving that the present application strictly controls the weight ratio of sodium stearate and palmitic acid, so that the modification effect at this time is significantly improved compared with the modification effect when used alone, and further improves its ability to promote uniform dispersion; All indicators of Comparative Examples 1-2.4 are inferior to those of Example 1.1, which proves that the present application bonds the components of the rare earth complex fluorescent material. When preparing the rare earth complex fluorescent material, the small molecules of the isocyanate and the polycarbonate diol can form a uniform arrangement, and the small molecules of the rare earth complex are separated one by one, so that the fluorescent segments of the finally obtained rare earth complex fluorescent material have a certain distance between each other. Compared with directly blending the rare earth complex fluorescent material with other components, the bonding method effectively reduces the possibility of easy aggregation of the fluorescent segments and thus fluorescence quenching, thereby reducing the possibility of damage to the fluorescence intensity, so that the fluorescent anti-counterfeiting ink of the present application has good fluorescence intensity; All indicators of comparative examples 2.5-2.6 are inferior to those of example 1.1, which proves that the present application strictly controls the weight ratio of rare earth complex fluorescent material, ink binder, ethyl acetate, defoaming agent and antioxidant, so that the internal dispersion uniformity, fluorescence intensity and rheological properties of the fluorescent anti-counterfeiting ink finally obtained are more balanced and at a higher level.
[0063] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A fluorescent anti-counterfeiting ink, the raw materials used include rare earth complex fluorescent material, ink vehicle, ethyl acetate, defoaming agent and antioxidant in a weight ratio of (30-60): (20-50): 16: 2: 2, characterized in that: The raw materials used for the rare earth complex fluorescent material include rare earth complex, isocyanate and polycarbonate diol in a molar ratio of 1: (2.8-3): 1, and the preparation method thereof is as follows: The rare earth complex is dispersed in an organic solvent, and then isocyanate is added, heated and stirred, and the organic solvent is added after the temperature reaction, and then polycarbonate diol is added to the system, and the reaction is continued. Finally, a chain extender and a capping agent are added to obtain a rare earth complex fluorescent material.
2. The fluorescent anti-counterfeiting ink according to claim 1, characterized in that: The raw materials used for the rare earth complex include rare earth oxide, dihydroxymethyl propionic acid, α-thenoyl trifluoroacetone and o-phenanthroline in a molar ratio of (2-2.2):4:8:
4.
3. The fluorescent anti-counterfeiting ink according to claim 2, characterized in that: The rare earth oxides include europium oxide, gadolinium oxide and ytterbium oxide.
4. The fluorescent anti-counterfeiting ink according to claim 3, characterized in that: The molar ratio of europium oxide, gadolinium oxide and ytterbium oxide is 1:6.2:2.
8.
5. The fluorescent anti-counterfeiting ink according to claim 1, characterized in that: The weight ratio of the rare earth complex fluorescent material, ink connecting material, ethyl acetate, defoaming agent and antioxidant is 50:30:16:2:
2.
6. The fluorescent anti-counterfeiting ink according to claim 1, characterized in that: The raw materials used also include a fatty acid modified nano material dispersant, and the weight ratio of the fatty acid modified nano material dispersant to the total weight of other raw materials used is (11-12):
100.
7. The fluorescent anti-counterfeiting ink according to claim 6, characterized in that: The fatty acid modified nano material dispersant is prepared by the following method, specifically: The nanomaterial is heated, and then fatty acid is added to react, filtered, dried, and ball-milled to obtain a fatty acid-modified nanomaterial dispersant, wherein the weight ratio of the nanomaterial to the fatty acid is 100:(3-4).
8. The fluorescent anti-counterfeiting ink according to claim 7, characterized in that: The fatty acids include sodium stearate and palmitic acid.
9. The fluorescent anti-counterfeiting ink according to claim 8, characterized in that: The weight ratio of the sodium stearate to palmitic acid is 1:
1.
10. A method for preparing the fluorescent anti-counterfeiting ink according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: uniformly mixing all the raw materials used, and finally obtaining the fluorescent anti-counterfeiting ink.